Comparing Scenario and Semi-structured Interviews in Inclusive Education Research: Perspectives of Trainee Teachers on Addressing Children with Special Educational Needs - Turgut Anıl Karlıdağ; Oğuzhan Hazır (e-Kafkas Eğitim Araştırmaları Dergisi)
The scenario interview technique allows researchers to explore the complex and context-dependent nature of inclusive teaching practices. This study was designed using a phenomenological approach, and 14 trainee teachers volunteered to participate. The results showed that each participant expressed their own ideas according to each scenario and demonstrated their understanding of how to address and overcome the student's problem in special education. Therefore, the scenario interview data collection technique can be utilized in educational studies to gain insights into participants' perspectives, decision-making processes, interpretations of behaviour towards themselves or an organization, by using real or hypothetical events on specific topics.